1994
DOI: 10.2307/797089
|View full text |Cite
|
Sign up to set email alerts
|

Locally Undesirable Land Uses in Minority Neighborhoods: Disproportionate Siting or Market Dynamics?

Abstract: The environmental justice movement contends that people of color and the poor are exposed to greater environmental risks than are whites and wealthier individuals. The movement charges that this disparity is due in part to racism and classism in the siting of environmental risks, the promulgation of environmental laws and regulations, the enforcement of environmental laws, and the attention given to the cleanup of polluted areas.' To support the first charge-that the siting of waste dumps, polluting factories,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
200
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(202 citation statements)
references
References 0 publications
0
200
0
2
Order By: Relevance
“…How do we measure progress? Thus, our society finds itself in the awkward position of trying to put environmental justice principles into practice while at the same time debat-ing the meaning of the term and its implications for Ž decision making Greenberg, 1993;Been, 1994;Zimmerman, 1994;Cushman, 1998;Sexton and Zimmerman, . 1999 .…”
Section: Introductionmentioning
confidence: 99%
“…How do we measure progress? Thus, our society finds itself in the awkward position of trying to put environmental justice principles into practice while at the same time debat-ing the meaning of the term and its implications for Ž decision making Greenberg, 1993;Been, 1994;Zimmerman, 1994;Cushman, 1998;Sexton and Zimmerman, . 1999 .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found income and poverty to be consistently associated with hazard presence in the expected direction: as environmental hazard presence increases, incomes decrease and poverty rates increase (Ash and Fetter, 2004;Been, 1994;Charkraborty and Armstrong, 1997;Derezinski et al, 2003;Downey, 2003;Hamilton, 1995;Krieg, 1995;Lester et al, 2001;McMaster et al, 1997;Mohai and Bryant, 1992;Morello-Frosch et al, 2001;Oakes et al, 1996;Ringquist, 1997;Stretesky and Hogan, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although many studies have found strong evidence of environmental racial inequality (Ash and Fetter, 2004;Been, 1994;Downey, 1998Downey, , 2003Hamilton, 1995;Krieg and Faber, 2004;Mohai and Bryant, 1992;Morello-Frosch et al, 2001;Ringquist, 1997;Stretesky and Hogan, 1998;Stretesky and Lynch, 2002), some have found evidence of environmental racial inequality for some minority groups but not others (Brown et al, 1997;Mennis and Jordan, 2005;Pastor et al, 2002;Sadd et al, 1999) and some have found only weak evidence of environmental racial inequality or none at all (Anderton et al 1994a(Anderton et al , 1994bAtlas 2002;Bowen et al 1995;Clark et al, 1995;Derezinski et al, 2003;Oakes et al, 1996;Yandle and Burton, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to enhancing our understanding of environmental inequities (Baden and Coursey, 1997;Been, 1994;Krieg, 1995;Pulido et al, 1996;Yandle and Burton, 1996) 10 , historical research has also problematized racism by asking, what if the people came first? While potentially a fruitful line of inquiry, the narrow conception of racism informing the literature has resulted in challenges to claims of racism: What were the intentions of the responsible parties?…”
Section: Siting and Intentionality In Discrete Acts Of Racismmentioning
confidence: 99%